British economic development in South East Asia, 1880 - 1939. Volume 1 - Sunderland, David, 1958- (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2017)
This collection focuses on the economic development of the areas of SE Asia with which Britain had a trading relationship. Covering 1880-1939, the economic growth of the region is revealed through a selection of rare primary resources organized thematically with sections dedicated to agriculture, mining, trade, labour, finance and infrastructure.
part Agriculture -- part Watson, The Land Laws and Land Administration of the Federated Malay States (1908) -- chapter R. G. Watson, the Land Laws and Land Administration of the Federated Malay States (1908) -- part Grist, Malaya: Agriculture,'Land Tenure' (1929) -- chapter D. H. Grist,Malaya: Agriculture(1929), extract -- part Anon., The Land Regulations of British North Borneo, 1894: Approved by the Court of Directors of the British North Borneo Company, on the 5th Day of June, 1894 (1894) -- chapter Anon.,The Land Regulations of British North Borneo, 1894: Approved by the Court of Directors of the British North Borneo Company, on the 5th Day of June, 1894(1894) -- part Wray, Notes on Perak with a Sketch of its Vegetable, Animal and Mineral Products (1886) -- chapter L. Wray Jr,Notes on Perak with a Sketch of its Vegetable, Animal and Mineral Products(1886), extract -- part Anon., General Cultivation (1924) -- chapter Anon.,General Cultivation(1924) -- part G. E. Shaw, Malay Industries. Part 3. Rice Planting (1911) -- chapter G. E. Shaw,Malay Industries. Part 3. Rice Planting(1911), extract -- part Anon.,'Report of the Rice Cultivation Committee, 1931. Volume 1' (1931) -- chapter Anon.,'Report of the Rice Cultivation Committee, 1931. Volume 1', extract -- part Jordan,'Memorandum. Rice Cultivation by Chinese in Malaya', 11th October, 1930' (1930) -- chapter A.B.Jordan,'Memorandum. Rice Cultivation by Chinese in Malaya', 11th October, 1930', extract -- part Noel-Paton, Burma Rice (1912) -- chapter F.Noel-Paton, Burma Rice (1912) -- part Macfadyen, Rubber Planting in Malaya (1924) -- chapter E. Macfadyen, Rubber Planting in Malaya (1924), extract -- part Grist, Nationality of Ownership and Nature of Constitution of Rubber Estates in Malaya (1933) -- chapter D.H. Grist, Nationality of Ownership and Nature of Constitution of Rubber Estates in Malaya (1933) -- part Anon., Report of the Commission Appointed by His Excellency the High Commissioner for the Malay States to Enquire Whether any Action Should be Taken by the Government to Give Protection or Asssistance to the Rubber Industry (1918) -- chapter Anon., Report of the Commission Appointed by His Excellency the High Commissioner for the Malay States to Enquire whether any Action Should be Taken by the Government to Give Protection or Assistance to the Rubber Industry (1918) -- part Anon., Economic Survey of the Sugarcane Industry in the East Central, Tenasseria and Northern Agricultural Circles (1926) -- chapter Anon., Economic Survey of the Sugarcane Industry in the East Central, Tenasseria and Northern report of a mission Agricultural Circles (1926) -- part Grist, Malaya: Agriculture,'Oil Palms' (1929) -- chapter D. H. Grist, Malaya: Agriculture (1929), extract -- part Coghlan, Coconut Industry in Malaya (1924) -- chapter H. L. Coghlan, Coconut Industry in Malaya (1924), extract -- part Anon., Report of a Committee ... To Investigate and Report on the Present Economic Condition of the Coconut and Other Vegetable Oil Producing Industries in Malaya (1934) -- chapter Anon., Report of a Committee ... to Investigate and Report on the Present Economic Condition of the Coconut and Other Vegetable Oil Producing Industries in Malaya (1934), extract -- part Cubitt, Wood in the Federated Malay States: Its Use, Misuse and Future Provision (1920) -- chapter G. E. S. Cubitt, Wood in the Federated Malay States: Its Use, Misuse and Future Provision (1920), extract -- part Mead, Annual Report on Forest Administration in Malaya Including Brunei, 1939 (1939) -- chapter J. P. Mead, Annual Report on Forest Administration in Malaya including Brunei, 1939 (1939) -- part'Notes on Forest Exploitation and the Forestry Service' in British North Borneo and Dutch N.E Borneo' ([1937]) -- chapter'Notes on Forest Exploitation and the Forestry Service in British North Borneo and Dutch N.E Borneo' ([1937]) -- part Anon., Forestry in Brunei: A Statement Prepared for the British Empire Forestry Conference, South Africa, 1935 (1935) -- chapter Anon., Forestry in Brunei: A Statement Prepared for the British Empire Forestry Conference, South Africa, 1935 (1935) -- part Anon., Burma Teak(l935) -- chapter Anon., Burma Teak (1935),extract -- part German, Handbook to British Malaya (1927) -- chapter R. L. German, Handbook to British Malaya (1927), extract -- part Winstedt, Malay Industries. Part 2. Fishing, Hunting and Trapping (1909) -- chapter R. Winstedt, Malay Industries. Part 2. Fishing, Hunting and Trapping (1909), extract -- part Maxwell, Preliminary Report on the Economic Position of the Fishing Industry of the Straits Settlements and Federated Malay States (1919) -- chapter C. Maxwell, Preliminary Report on the Economic Position of the Fishing Industry of the Straits Settlements and Federated Malay States (1919), extract.
Keywords: Economic development -- Southeast Asia -- History -- 19th century -- Sources; Economic development -- Southeast Asia -- History -- 20th century -- Sources